Identification of occult active infection using PET‐CT in a combined liver‐kidney transplant candidate. Issue 6 (3rd November 2017) - Al Shakarchi, Julien; Neil, Desley; Lipkin, Graham; Elsharkawy, Ahmed; Inston, Nicholas
Abstract: This case describes a patient being considered for combined liver‐kidney transplantation for Caroli's disease with a failed renal transplant. A chronic septic focus could not be located with standard imaging techniques, such as ultrasonography and computed tomography. This case report highlights the observation that a retained non‐functioning transplant can be the cause of fever of unknown origin and PET‐CT can be useful in diagnosing these challenging cases.